2006
DOI: 10.1371/journal.ppat.0020003
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes Invades the Epithelial Junctions at Sites of Cell Extrusion

Abstract: Listeria monocytogenes causes invasive disease by crossing the intestinal epithelial barrier. This process depends on the interaction between the bacterial surface protein Internalin A and the host protein E-cadherin, located below the epithelial tight junctions at the lateral cell-to-cell contacts. We used polarized MDCK cells as a model epithelium to determine how L. monocytogenes breaches the tight junctions to gain access to this basolateral receptor protein. We determined that L. monocytogenes does not ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
205
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(223 citation statements)
references
References 86 publications
16
205
0
2
Order By: Relevance
“…Using rabbit ligated ileal loops and Madin-Darby canine kidney (MCDK) cells as a polarized epithelium model, it has been proposed that L. monocytogenes does not disrupt the enterocyte tight junctions to gain access to E-cadherin, but instead interacts with exposed E-cadherin at sites where apoptotic cells are expelled and detached from the epithelium by extrusion, suggesting that L. monocytogenes exploits the dynamic nature of epithelial renewal and junctional remodeling in small intestinal villi to breach this barrier (Fig. 3) (Pentecost et al 2006). Of note, infection of wild-type mice intragastrically with a L. monocytogenes strain expressing a modified InlA that binds murine Ecadherin suggested that InlB also participates in bacterial internalization at small intestine villi; experiments in MDCK cells suggest that InlB does not act as an adhesin but rather accelerates bacterial internalization by promoting endocytosis of junctional components (Pentecost et al 2010).…”
Section: Role Of Inla and Inlb In The Traversal Of The Host Barriers mentioning
confidence: 99%
“…Using rabbit ligated ileal loops and Madin-Darby canine kidney (MCDK) cells as a polarized epithelium model, it has been proposed that L. monocytogenes does not disrupt the enterocyte tight junctions to gain access to E-cadherin, but instead interacts with exposed E-cadherin at sites where apoptotic cells are expelled and detached from the epithelium by extrusion, suggesting that L. monocytogenes exploits the dynamic nature of epithelial renewal and junctional remodeling in small intestinal villi to breach this barrier (Fig. 3) (Pentecost et al 2006). Of note, infection of wild-type mice intragastrically with a L. monocytogenes strain expressing a modified InlA that binds murine Ecadherin suggested that InlB also participates in bacterial internalization at small intestine villi; experiments in MDCK cells suggest that InlB does not act as an adhesin but rather accelerates bacterial internalization by promoting endocytosis of junctional components (Pentecost et al 2010).…”
Section: Role Of Inla and Inlb In The Traversal Of The Host Barriers mentioning
confidence: 99%
“…The way by which L. monocytogenes gets access to the adherens junction protein Ecadherin and the mechanism by which bacteria cross the intestinal barrier were not known until recently. It had been proposed that L. monocytogenes access to E-cadherin may be facilitated when extruding epithelial cells detach from the tips of intestinal microvilli, thereby exposing Ecadherin to the luminal side of the intestine (Pentecost et al 2006). This was shown in vitro and correlated with a colocalization of bacteria with extruding cells in rabbit ileal loop in vivo.…”
Section: Translocation Across Enterocytesmentioning
confidence: 99%
“…) Sabet et al, 2008). Although cellular mechanisms of infection are becoming more clear (Hamon et al, 2006), we still have much to learn about the intestinal (Gahan & Hill, 2005;Pentecost et al, 2006), utero-placental (Bakardjiev et al, 2006;Lecuit et al, 2004) and neurological phases of infection (Drevets & Bronze, 2008).…”
Section: Introductionmentioning
confidence: 99%